Secondary Spontaneous Pneumothorax in Recurrent Pulmonary Tuberculosis: A Case Report - Dhea Aprilia; Buti Ariani Ar Nur; Ulfahimayati Ulfahimayati (Medical and Health Journal, 2026)
Background: Secondary spontaneous pneumothorax is a potentially life threatening complication that may occur in patients with underlying pulmonary diseases, including pulmonary tuberculosis. In recurrent pulmonary tuberculosis, residual lung damage such as cavitation, fibrosis, and bullae increases the risk of alveolar rupture, leading to pneumothorax. Objective: To describe the clinical presentation, diagnostic findings, management, and outcome of a patient with secondary spontaneous pneumothorax associated with recurrent pulmonary tuberculosis. Case Presentation: A 21 year old male with a history of pulmonary tuberculosis two years prior presented to the emergency department with sudden onset shortness of breath and pleuritic chest pain. Physical examination and chest radiography revealed an avascular radiolucent area in the right lung, consistent with pneumothorax. A rapid molecular sputum test was positive for Mycobacterium tuberculosis. A diagnosis of right sided secondary spontaneous pneumothorax due to recurrent pulmonary tuberculosis was established. The patient underwent needle decompression followed by the placement of a water sealed drainage (WSD) system. Anti tuberculosis therapy was reinitiated according to the national treatment protocol. Results: Follow up chest radiographs demonstrated progressive lung re expansion, accompanied by significant clinical improvement. The patient’s condition stabilized, and no further complications were observed during hospitalization. Conclusion: Secondary spontaneous pneumothorax in patients with recurrent pulmonary tuberculosis represents an emergency condition that requires rapid diagnosis and appropriate management. The combination of WSD insertion and anti tuberculosis therapy proved effective in promoting lung re-expansion and improving clinical outcomes. Heightened clinical awareness of this complication is essential to improve prognosis in patients with recurrent pulmonary tuberculosis.